Geological map of the San Donato – Costa Thrust Zone, Belluno Thrust System, eastern Southern Alps (northern Italy). Issue 2 (1st December 2021) - Zuccari, Costantino; Vignaroli, Gianluca; Viola, Giulio
ABSTRACT: We present a 1:7500 scale geological map of part of the footwall of the south verging Belluno Thrust of the seismically active eastern Southern Alps of northern Italy. We report a previously unknown thrust zone, the "San Donato-Costa Thrust Zone", that cuts across the local Meso-Cenozoic stratigraphic succession. 1:2500 and 1:5000 geological mapping, in combination with the revision and improvement of the local lithostratigraphy and detailed structural analysis, provided new insights into the thrust geometry and the setting of the greater area it deforms. We show that the recorded deformation style (e.g. folding vs. faulting) exhibits notable variations within the affected Meso-Cenozoic stratigraphic succession, with shortening accommodated by fold trains and several subparallel thrust splays with variable amounts of stratigraphic offset cumulated during repeated faulting. Our results contribute to a better definition of folding and faulting within the Mesozoic carbonate multilayer system of the eastern Southern Alps.